(3TQM GdaQGFV GdSLGhfOjIs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj,, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s
(3ChdgG (B:s
(3Ojhfg ef LejY eG Hbj ef eGdg Cj Ke jHOC HbVGA Ojhfg ef Lejg eGdg GdKGfj HYO GdJLgjRs
(3BNQgG (B:s
(3ef UGMHg eG hQK efg abO GLJeY dCe cd efgeG YTQhf hdHfJg SJhf hdehdGg YTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 7s
(3eYLe GdeDdajf (B2 / 514 (3, (B515s
(3cTa GdXfhf (B2 / 12487s
(3gOjI GdYGQajf (B1 / 728s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs